An Examination of the Agreement between Self-reported Diabetes and Paraclinical Tests, Medical Records, and Clinical Examinations: Insights from the Shahedieh Cohort Study, Yazd, Iran - Farzan Madadizadeh; Mahdieh Momayyezi; Hossein Fallahzadeh (Journal of Caring Sciences)
Introduction: Many researchers utilize self-reports to evaluate the prevalence of diseases. However, the accuracy of these self-reports remains uncertain in various studies. The objective of this particular study was to validate self-reported cases of diabetes among adults aged 35-70 years participating in the Shahedieh Cohort Study (SHCS). Methods: This cross-sectional study was conducted using data from the first phase of SHCS during 2015-2017. The study included 1000 Iranian adults aged 35-70 years. The Gold standard for diabetes was determined by measuring fasting blood sugar (FBS) and evaluating the history of treatment and use of diabetes medications. To assess self-report validity, various statistical indices such as sensitivity, specificity, positive and negative predictive values (NPVs), accuracy, positive likelihood ratio (LR+), negative likelihood ratio (LR-) and AUC were used. The agreement between self-reported diabetes and the gold standard was assessed using kappa statistics. All statistical analyses were performed using SPSS version 13 and R 4.3.1 software. Results: The study findings indicated that the prevalence of diabetes was 18% according to self-report and 19.9% according to the gold standard measurement. The self-report accuracy was 95.67%. There was perfect agreement (kappa=0.86) between the self-report and gold standard criteria. The AUC, sensitivity and specificity of self-reported diabetes were 0.937, 93.82% and 96.08%, respectively. Additionally, the results suggested that the self-report of diabetes was more valid in individuals with a normal body mass index (BMI) and without a family history of diabetes in first-degree relatives. Conclusion: The results showed that in the absence of diabetes control programs, self-report of diabetes is reliable and recommended.